An in-vitro Comparison of Calcium Uptake by Intact Enamel after Using two Types of Casein Phosphopeptide-Amorphous Calcium Phosphate Paste - S Hekmatfar; K Jafari; S Mohammadpour (Islamic Azad University, 2018)
Background and aim: Dental caries is one of the most common childhood diseases worldwide. The implementation of strategies that facilitate the prevention of early dental caries and interrupt its progression has been recently advocated. It has been reported that casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) derived from casein reduces tooth demineralization and enhances the remineralization process. The aim of this in-vitro study was to assess the efficacy of two types of CPP-ACP paste in calcium uptake by enamel surfaces. Materials and methods: Forty premolars were longitudinally dissected into experimental and control halves, and were coated with nail varnish, except for an enamel window of 4×4 mm. The samples were subjected to cycling in a demineralizing solution and were divided into two groups of GC Tooth Mousse CPP-ACP paste and Misswake CPP-ACP paste. The calcium contents of each half were examined using the acid etch enamel biopsy technique and were measured by atomic absorption. The values were statistically analyzed using Kolmogorov-Smirnov test and one-way analysis of variance (ANOVA). Results: The enamel surfaces treated with the pastes exhibited higher calcium contents compared to the controls. There was a significant difference between GC Tooth Mousse CPP-ACP paste and Misswake CPP-ACP paste in terms of calcium uptake; a higher calcium uptake was witnessed with GC Tooth Mousse CPP-ACP paste than with Misswake CPP-ACP paste (P<0.05). Conclusion: Misswake CPP-ACP paste presented some protective potentials; however, the samples treated with GC Tooth Mousse CPP-ACP paste were better able to uptake calcium. These pastes could be considered as effective means for the prevention of dental caries in susceptible patients.